2020
DOI: 10.1007/s11837-020-04452-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature, Time, and Cooling Rate on the Mineralogy, Morphology, and Reducibility of Iron Ore Sinter Analogues

Abstract: Analogue sinter tablets were produced at temperatures between 1250°C and 1320°C, with a range of hold times and cooling rates. Platy silico-ferrite of calcium and aluminum (SFCA) morphology was identified in samples produced at 1250°C using reflected light microscopy; however, quantitative x-ray diffraction (XRD) identified the presence of the SFCA phase, with no SFCA-I detected. This proves that the platy SFCA morphology common in analysis by reflected light microscopy cannot be attributed to the SFCA-I miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Therefore, in determining the reduction rate of the sinter, the influence of the microstructure on the diffusion of the reducing gas is more significant than that of the ICR due to the formation of the SFCA phase. Kato et al [24] and Harvey et al [25] have also reported that the microstructure is a more important influencing factor than the iron oxide reactivity in sinter reduction. The GMT rate constants (R.D > 33% region) were derived from the results of this experiment, and the results of the porosity analysis on the sample prior to reduction are shown in Figure 10.…”
Section: Influence Of Al2o3 On the Metastable Samplementioning
confidence: 99%
“…Therefore, in determining the reduction rate of the sinter, the influence of the microstructure on the diffusion of the reducing gas is more significant than that of the ICR due to the formation of the SFCA phase. Kato et al [24] and Harvey et al [25] have also reported that the microstructure is a more important influencing factor than the iron oxide reactivity in sinter reduction. The GMT rate constants (R.D > 33% region) were derived from the results of this experiment, and the results of the porosity analysis on the sample prior to reduction are shown in Figure 10.…”
Section: Influence Of Al2o3 On the Metastable Samplementioning
confidence: 99%
“…Tejbir SINGH, 1) Subhasish MITRA, 1) Damien O'DEA, 2) Lydia KNUEFING 3) and Tom HONEYANDS 1) * 1) Centre for Ironmaking Materials Research, School of Engineering, The University of Newcastle, Callaghan, NSW, 2308 Australia.…”
Section: Quantification Of Resistance and Pressure Drop At High Tempe...mentioning
confidence: 99%
“…The liquid phase served as a binding material between residual iron oxide particles. When the iron ore sinter was cooled, SFCA, SFCA-I, and other calcium ferrites were formed [37][38][39]; dicalcium silicate, alumina, quartz, and glass were also present as minor mineral phases. SFCA in the iron ore sinter appeared in different forms (columnar, acicular, prismatic, platy, etc.…”
Section: Phase Analysis Of Iron Ore Sintermentioning
confidence: 99%
“…Most of the sinter quality (reducibility and degradation degree) was affected by the amount and shape of SFCA [35,[40][41][42][43][44][45][46][47]. As the cooling rate increased, the fractions of columnar and platy type (SFCA, SFCA-I) increased [39]. Furthermore, the fraction of columnar type increased with the Al 2 O 3 content.…”
Section: Phase Analysis Of Iron Ore Sintermentioning
confidence: 99%
See 1 more Smart Citation